Eksperimen Pembelajaran Matematika Pada Materi Himpunan Dengan Strategi Numbered Heads Together (NHT) Dan Think Pair Share (TPS) Terhadap Hasil Belajar Matematika Ditinjau Dari Kemandirian Belajar Siswa Kelas VII Semester Genap Di Smp Al-Islam Kartasura Tahun Ajaran 2015/2016 - Darmaningsih, Eka Nurhayati; , Idris Harta, M.A., Ph.D (2016)
The research is conducted to analyze: (1) the different effects of using strategy Numbered Heads Together, Think Pair Share and expository on learning outcomes mathematics, (2) the different effects of independency of studying on learning outcomes mathematics, (3) interaction between the effects of using strategy Numbered Heads Together, Think Pair Share and expository with the independency on learning outcomes mathematics. The type of research is quantitative approach with quasi experiments design. The population in this research is the whole students of seven SMP Al-Islam Kartasura year academic 2015/2016. The technique of collecting data in this research is to use cluster random sampling. The method of collecting data is using test, inquiry, and documentation. The technique of using analysis is various using two cells. The result of analyzing data using significant level 0,05 shows that: (1) there are different effects of studying strategy Numbered Heads Together, Think Pair Share and expository on learning outcomes mathematics, with FA = 7,026 (2) there is the independency different effect of studying on learning outcomes mathematics, with FB = 28,532 (3) no interaction between the using of strategy Numbered Heads Together, Think Pair Share and expository using the independency of studying on learning outcomes mathematics, with FAB = 0,352.